Potential of non-thermal processing for food preservation in Southeast Asian countries - Mohd Adzahan, Noranizan; P., Benchamaporn (Universiti Putra Malaysia Press, 2007)
The application of non-thermal processing technology (NTP) is increasing within the food industry. The absence of heat in this technology offer some advantages such as the sensory and nutritional attributes of the product remaining unaffected, thus yielding products with better quality compared to traditional processing methods. Suitability of technology for a certain application varies according to the nature of the reason and the purpose for processing. Some NTP has long been used in the food industry in Southeast Asia, but most are still at the initial stage of research. Despite several existing challenges, these technologies have the potential to be taken up as an alternative to processing of value-added food products especially now when consumer and trade demands as well as economic strength in the region is changing.